Customer Care and Increased Clientele: A Case Study of Centenary Bank Kabale Branch. - Tusiime, Bridget (Kabale University, 2024)
The main purpose of the study was to investigate the effect of customer care and increased clientele using a case study of Centenary Bank Kabale Branch. The study was guided by the following objectives; to assess the level of increased clientele of Centenary Bank Kabale Branch in Kabale district, to establish the influencing increased clientele at Centenary Bank Kabale Branch and to establish the relationship between customer care and increased clientele at Centenary Bank Kabale Branch. The study adopted a descriptive research design comprising of both qualitative and quantitative approaches. The study consisted of clients, employees, and branch managers. The researcher used a sample size of 30 respondents. The study was based on questionnaires and interviews. The collected data was analyzed manually using tallies and the responses of the subjects were then categorized in frequency counts and score tables with varying percentages calculated and later tabulation method was used to present data. The study concludes that on the theme of the level of increased clientele of Centenary Bank Kabale Branch in Kabale district, the study findings revealed that the main forms of increased clientele in this bank were Referrals and word-of-mouth, Marketing and advertising, Digital channels, and Community engagement. On the theme of the factors influencing increased clientele at Centenary Bank Kabale Branch, it was found that the fact that 50% of respondents highlighted quality customer service indicates that it is the cornerstone of client retention and acquisition. Personalized interactions and efficient problem resolution create a loyal customer base, the 27% response rate for product and service innovation shows that clients value a bank that continually improves and diversifies its offerings. Staying ahead with innovative products can attract a varied clientele looking for tailored financial solutions, with 13% of respondents recognizing marketing and branding, it underscores the need for the bank to maintain a visible and positive public image to attract potential clients, and although only 10%, the emphasis on digital transformation highlights the growing trend towards digital banking solutions. As more clients prefer online and mobile banking, this factor will likely gain more significance. The study recommends that the bank should prioritize the development of its online and mobile banking services, ensuring they are user-friendly and secure and the bank should continue to invest in diverse marketing campaigns.